Evaluation of Tax Debt Management for Bankrupt Taxpayers in Indonesia - Tosan Yanuar Rachmadi; Yulianti Abbas (LPPM STIE Krakatau, 2025)
Purpose: This study aims to evaluate tax debt management for taxpayers who are bankrupt in Indonesia, based on successful tax debt management. Methodology/approach: This study is a literature review that compiles and synthesizes data from Indonesian Tax Collection Law with Distress Warrant Law, General Tax Provisions and Procedures Law, Bankruptcy and Postponement of Debt Payment Obligations Law, Minister of Finance Regulation. This study also integrates previous research to evaluate tax debt management for bankrupt taxpayers in Indonesia, based on successful tax debt management. Results/findings: Persuasive communication with bankrupt taxpayers is deemed nonessential in the context of tax debt management within bankruptcy proceedings. Standardized procedures were in place within the Directorate General of Taxes prior to resorting to law enforcement measures for debt collection from bankrupt taxpayers. These measures encompass a spectrum of enforcement tactics, including asset confiscation, imposition of travel restrictions (exit bans), and detainment in extreme circumstances. The Directorate General of Taxes assesses various criteria to determine the viability of collecting debt from bankrupt taxpayers, considering factors such as economic feasibility and practicality. Conclusions: The management of tax debt for bankrupt taxpayers in Indonesia follows a strict legal framework that emphasizes enforceability over negotiation. The study finds that the Directorate General of Taxes utilizes a set of standardized enforcement procedures—such as asset seizure, travel bans, and detainment—to ensure debt recovery, guided by principles of feasibility and efficiency. These mechanisms, while structured, tend to overlook the potential role of persuasive or rehabilitative strategies in tax collection. Therefore, while legal measures are effective to a certain extent, a more balanced approach that includes taxpayer engagement and policy innovation may improve long-term compliance and recovery rates. Limitations: This study did not conduct a comparative analysis of tax debt management for bankrupt taxpayers in Indonesia and similar practices in other countries. Such a comparison would elucidate how different jurisdictions address tax debt management for bankrupt taxpayers, and could offer valuable insights for overcoming collection challenges specific to Indonesia. By examining common practices in other countries, this study provides recommendations tailored to the Indonesian context to improve the effectiveness of tax debt collection from bankrupt taxpayers. Contribution: This study enriches the literature on how the Directorate General of Taxes manages bankrupt taxpayers to pay their debts.